Integration of Use Case Formal Template Using Mapping Rules - Swee, Yin Wong; Edwin, Mit; Jonathan, Sidi (2016)
The integration of use case and formal specification plays an essential role in addressing the issue of gaining the rigor and reliable software model such as formal model via easy and economic model such as object model. Although extensive research has been carried out on this Integration, however there is a huge challenge on bridging the gaps between natural language used In use case scenario and the mathematics model used in formal model. This Is mainly because of the differences In syntax and semantic of these two models. Natural language requirement is well documented that it is being inconsistent, inherently ambiguous, and incomplete even though natural language Is universal, widespread, and flexible. As a consequence, It may lead to misunderstanding and produce an incorrect and inaccurate analysis and design model. Therefore, this paper aims to propose a use case formal template and define a new set of mapping rules that Is used for formalizing UML use case by transforming use case scenarios which are written In natural language Into VDM++ formal specification. The formal verification for the generated VDM++ formal specification can be further conducted by adopting the existing support tool of VDM++ (i. e. VDM++ ToolBox) to verify the correctness of the specification.